Bioactive carbazole and quinoline alkaloids from Clausena dunniana. (July 2018) - Cao, Nankai; Chen, Yuemei; Ma, Xiaoli; Zeng, Kewu; Zhao, Mingbo; Tu, Pengfei; Li, Jun; Jiang, Yong
Abstract: Nine undescribed carbazole and quinoline alkaloids, named dunnines A–E, and 14 known analogues were isolated from the leaves and stems of Clausena dunniana. Their structures were elucidated on the basis of comprehensive analysis of NMR and HRMS spectroscopic data, and the absolute configurations were assigned via comparison of their specific rotations and calculated and experimental ECD data. (±)-Dunnines A–C and (±)-clausenawalline A are four pairs of biscarbazole atropisomers and (±)-dunnine D is a pair of dihydropyranocarbazole enantiomers. They were separated by chiral HPLC to obtain the optically pure compounds. Three compounds showed weak inhibitory effects on nitric oxide production stimulated by lipopolysaccharide in BV-2 microglial cells (IC50  > 50 μM); five compounds could significantly promote insulin secretion in HIT-T15 cell line (1.9–3.1-fold of the control, p  < 0.01) at 40 μM, and nine compounds could inhibit the apoptosis of PC12 cell induced by 6-hydroxydopamine with IC50 values in the range of 10.9–47.2 μM. Graphical abstract: Nine undescribed carbazole and quinoline alkaloids, along with 14 known analogues, were isolated from Clausena dunniana H. Lév. (Rutaceae). Highlights: Nine undescribed alkaloids were isolated from Clausena dunniana. Four pairs of biscarbazole atropisomers were chirally separated. A pair of dihydropyranocarbazole enantiomers were chirally separated. Five compounds exhibited significant insulin-release stimulating activities. Nine compounds showed potent neuroprotective effects.